Aktualisasi Nilai-Nilai Hukum Islam dalam Kriminalisasi Tindak Pidana Penyimpangan Seksual dalam KUHP Baru - Ridho Rinaldo (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Sexual deviant behavior develops along with the times to lead to crime, while Islam strongly opposes sexual deviant behavior. Indonesia as a nation with the majority of Muslims, ideally the values of Islamic law can be actualized in the national criminal law. However, in reality, the new Criminal Code does not explicitly mention sexual deviant behavior, and this results in the low legal certainty of the act. This research aims to identify the behavior of sexual deviation in the view of Islamic law as well as the actualization of Islamic legal values in the criminalization of sexual deviation in the new Criminal Code. The type of research method used in this study is normative juridical with statutory and conceptual approaches. The results of this study found that the behavior of sexual deviation in the view of Islamic law has 3 kinds, against humans, animals and inanimate objects. The form of actualization of Islamic legal values related to sexual deviant behavior in the new Criminal Code is identified in the form of: homosexuality, lesbidan, pedophila, bestiality or zoophilia, necrophilia, inces, digisexual, exhibitionism, frotteurism and thus, the New Criminal Code has regulated acts that can be categorized as sexual perversion as in the view of Islamic legal values.